The Effect of Compensation and Work Environment on Work Productivity through Job Satisfaction - Lestari, Adinda Dwi (Universitas Negeri Surabaya, 2025)
This study aims to explain the effect of compensation and work environment on work productivity through job satisfaction. This research applies a quantitative approach, with a total population of 58 employees and a sample of 38 employees. The Structural Equation Modeling Partial Least Square (SEM-PLS) technique was applied in this study to analyse the data with the help of SmartPLS software version 4.1. The results obtained from this study indicate that compensation and work environment have a significant positive effect on job satisfaction, compensation and work environment have no significant effect on work productivity, and job satisfaction has a significant positive effect on work productivity. In the indirect effect analysis, job satisfaction is proven to mediate the effect of compensation and work environment on productivity. The research implications that can be applied to companies are that companies need to pay more attention to aspects that can affect employee productivity levels, one of which is related to work facilities, namely improving company network access; through a good and smooth network, employees can work effectively and do not hinder the customer service process. The company needs to pay attention to the job satisfaction employees feel towards the compensation received. Branch leaders must also give awards or appreciation to employees who have achieved work targets. In addition, the company needs to organise family gathering activities for all employees; these activities can create comfort for employees and strengthen relationships between superiors and employees.